Andreev reflection mediated by Majorana zero modes in T-shaped double quantum dots - Sun, Lian-Liang; Liu, Jia (Frontiers in Physics, 2022)
We study theoretically the Andreev reflection processes in T-shaped double quantum dots (TDQDs) by using the nonequilibrium Green's function technique. One of the TDQDs is coupled to the Majorana zero modes (MZMs) prepared at the ends of a topological superconductor nanowire, and simultaneously to one metallic and another superconductor leads. Our results show that the in-gap state originated from the proximity effect due to the superconductor lead is sensitive to the existence of MZMs. The local density of states (LDOS) of the spin-up electrons, which are directly coupled to the MZMs, has an Fano antiresonance at the in-gap state. Whereas that of the spin-down electrons, which are free from hybridization to the MZMs due to the helical property of the latter, has a Lorentzian resonance at the same state. The differential Andreev conductance of both the two spin directions exhibits Fano-type resonance, but with different tails' direction. The in-gap state is also significantly influenced by the energy level and coupling strength of the other side-coupled dot, as well as the MZM-MZM interaction.